Preserving Wayang Golek: The Rationale of Radio Komunitas Seni dan Budaya Maja FM Program Selection - Anwar, Rully Khairul; Besthari, Bian; Damayani, Ninis Agustini; Khadijah, Ute Lies Siti (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2024)
Wayang Golek as an integral part of the Sundanese culture, is at risk due to globalization and modern influences. To counter this, RKSB Maja FM, a community radio in Bandung, West Java, has initiated the